2002
DOI: 10.1017/s1431927602010346
|View full text |Cite
|
Sign up to set email alerts
|

The Pros and Cons of Apoptosis Assays for Use in the Study of Cells, Tissues, and Organs

Abstract: Programmed cell death or apoptosis occurs in many tissues during normal development and in the normal homeostasis of adult tissues. Apoptosis also plays a significant role in abnormal development and disease. Increased interest in apoptosis and cell death in general has resulted in the development of new techniques and the revival of old ones. Each assay has its advantages and disadvantages that can render it appropriate and useful for one application, but inappropriate or difficult to use in another. Understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
8

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 36 publications
3
102
0
8
Order By: Relevance
“…1). LTR accumulates within dead and dying cells, allowing us to identify areas of cell death in whole-mount embryos, and has been used previously to study apoptosis in the embryonic mouse (Zucker et al, 1998;Watanabe et al, 2002).…”
Section: Neural Crest Cells Arementioning
confidence: 99%
“…1). LTR accumulates within dead and dying cells, allowing us to identify areas of cell death in whole-mount embryos, and has been used previously to study apoptosis in the embryonic mouse (Zucker et al, 1998;Watanabe et al, 2002).…”
Section: Neural Crest Cells Arementioning
confidence: 99%
“…5, 2006 THYMUS HISTOPATHOLOGY 661 FIGURE 4.-(Continued) in the number of apoptotic cells should be noted only after comparison with controls. Although various methodologies are available for evaluating apoptosis (stained resin sections, DNA laddering, TUNEL, annexin V, caspase-3 activity assays, mitochondrial assays, vital dyes and lysotracker red), each assay has its advantages and disadvantages that can render it appropriate and useful for one application but inappropriate or difficult to use in another (Watanabe et al, 2002). Transmission electron microscopy ( Figure 2) is considered the "gold standard" for the evaluation of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…1) This staining pattern correlates to the spatial location of cell death staining with classical vital dyes (e.g. Nile blue, neutral red, acridine orange) and other apoptotic detection methods used to determine cell death during normal embryological development or embryological toxicology (22,23,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Sulik and coworkers have compared NBS and LT stains and shown that they stain the same regions (e.g.…”
Section: Lt Correlation With Cell Deathmentioning
confidence: 95%